2019
DOI: 10.3390/en12081464
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Freeze/Thaw Cycles on Mechanical and Thermal Properties of Masonry Wall and Masonry Wall Materials

Abstract: In this study, the influence of freeze/thaw cycles on the mechanical and thermal properties of bricks and mortar as building parts of masonry walls, as well as the influence on the masonry wall itself is investigated. At the material level, the influence of freeze and thaw cycles on the mechanical and thermal properties of masonry components (bricks and mortar) was investigated; at the construction level, the influence of freeze and thaw cycles on the mechanical and thermal properties of a masonry wall was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…An appropriate selection of the room to be analyzed according to their dimensions would reduce the energy consumption related to the thermal transmittance test. The scientific literature has analyzed that aspects such as the orientation of the room façade [41], the presence of moistures [42] or damages due to freezing [56] should be assessed before selecting the room or zone of the building to be analyzed; however, the need for selecting criteria to select the rooms which reduce the energy consumption of the test has not been analyzed. Figure 10 shows the effect of the criteria application of the room dimension (surface and length of the façade) on the tests simulated.…”
Section: Resultsmentioning
confidence: 99%
“…An appropriate selection of the room to be analyzed according to their dimensions would reduce the energy consumption related to the thermal transmittance test. The scientific literature has analyzed that aspects such as the orientation of the room façade [41], the presence of moistures [42] or damages due to freezing [56] should be assessed before selecting the room or zone of the building to be analyzed; however, the need for selecting criteria to select the rooms which reduce the energy consumption of the test has not been analyzed. Figure 10 shows the effect of the criteria application of the room dimension (surface and length of the façade) on the tests simulated.…”
Section: Resultsmentioning
confidence: 99%
“…Water has a higher thermal conductivity than the usual construction materials, so its presence could change the thermal behavior of the wall [44]. In this regard, the presence of moisture and freezing could imply considerable variations in the thermal transmittance value with respect to the same wall under normal conditions [29,44,45]. Finally, it is also necessary to consider the influence of the orientation on the thermal transmittance value.…”
Section: The Heat Flow Meter Methods and Temperature Measurement Methodsmentioning
confidence: 99%
“…Nevertheless, there is a lack of studies focused on the thermal characterization of superstructures of accommodation spaces in ships. This aspect is different with regard to the building sector, since the experimental methods of the thermal transmittance (e.g., the method from International Organization for Standardization (ISO) 9869-1 [24]) have been discussed in many research studies from the end of the 20th century [25][26][27] to nowadays [28][29][30][31]. In situ measurements have proved their usefulness to determine the current thermal performance of construction elements in existing buildings and as quality control in new buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Meng et al [28] found heat flux measurement errors of up to 26% but surface temperature measurement errors of only 6%. The most accurate results have been found to be achieved using an appropriate envelope orientation [29], a high thermal gradient during the tests [30], and unaltered elements [31].…”
Section: Introductionmentioning
confidence: 99%